2019
DOI: 10.26444/jpccr/102758
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic and clinical predictors of health-related quality of life in patients after myocardial infarction

Abstract: Introduction. Acute coronary syndrome is associated with a reduction in the patients' own perception of their quality of life (QoL). QoL is an important measure of the effectiveness of treatment; however, some of the predictors may be associated with a lower QoL assessment. The evaluation of QoL of patients after myocardial infarctions takes into consideration the socio-demographic and clinical predictors which can affect the level of health-related QoL Objective The aim of this study is to determine which soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
1
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 10 publications
1
1
0
3
Order By: Relevance
“…Study participants with secondary education as well as college and above educational level had better HRQoL than those with primary education and others. This finding is similar to a study done in Korea [36] and Poland [33]. Higher and better education can be an advantage for access to wider resources within the community and higher awareness of risk factors of MI.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Study participants with secondary education as well as college and above educational level had better HRQoL than those with primary education and others. This finding is similar to a study done in Korea [36] and Poland [33]. Higher and better education can be an advantage for access to wider resources within the community and higher awareness of risk factors of MI.…”
Section: Discussionsupporting
confidence: 90%
“…A cross-sectional study conducted in China showed that females had significantly lower scores of HRQoL [31]. A study conducted in Poland revealed the significant influence of education on almost all HRQoL domains, except the social domain [33]. Comorbidity is the number of coexisting diseases alongside the primary condition.…”
Section: Introductionmentioning
confidence: 99%
“…Quanto à caracterização sociodemográfica e clínica dos pacientes, observamos que a maioria dos pacientes submetidos à CRM pertencia ao sexo masculino, resultado que corrobora com outros estudos da literatura (JANSSEN et al, 2015;SOUSA et al, 2015;SILVA, L. N. et al, 2018;KAFADAR et al, 2018;KRZEMIŃSKA et al, 2019;ADHIKARI;BARAL, 2018;MELO;NEVES, 2019;CALLES et al, 2016;POOLE et al, 2017;ALEXANDRI et al, 2017;BANO et al, 2020;KSHIRSAGAR et al, 2020;NIELSEN et al, 2019;MURPHY et al, 2020;PERROTTI et al, 2019;AXELSSON et al, 2020;FORMENTINI et al, 2019;YANG et al, 2020;HOHLS et al, 2020;PACARIC et al, 2020).…”
Section: Discussionunclassified
“…Com relação a presença de companheiro e a situação profissional dos pacientes submetidos à CRM, a maior parte possuía companheiro e houve predominância de situação profissional inativa, corroborando com outros achados da literatura (JANSSEN et al, 2015;KRZEMIŃSKA et al, 2019;SILVA, L. D. C. et al, 2018;NIELSEN et al, 2019), assim como para os pacientes do grupo de correção valvar (ANJOS et al, 2016;OTERHALS et al, 2015;DORDETTO;PINTO;ROSA, 2016;RODRIGUES et al, 2020;CHEN et al, 2019;GIARETTA et al, 2018;HUSSAIN et al, 2018).…”
Section: Discussionunclassified
See 1 more Smart Citation